Dynamical Analysis of Virulence Evolution in Multistrain Infection Model Within Hosts (Journal of Nonlinear Modeling and Analysis, 2026)
Understanding the evolutionary patterns of viral virulence characteristics from a microscopic perspective is crucial for effectively combating viral mutations. This paper investigates the dynamics of virulence trait development within healthy cells following pathogen invasion using adaptive dynamics, building on a viral dynamics model that accounts for multiple infectious strains within hosts. Ignoring viral evolution, stability analysis of equilibria reveals the competitive exclusion principle. When viral virulence evolves, we assume that the infection rate of healthy cells and the mortality rate of infected cells are functions of virulence. We establish global stability conditions for the system and examine the evolutionary trajectory of viral virulence using adaptive dynamics. Our results indicate that mutant viruses can cause trait substitution. The evolutionary singular strategy is identified as a continuously stable strategy without producing evolutionary branching. Furthermore, we consider the influence of certain parameters in the system on the evolution of singular strategies.
Keywords: Viral infection model; adaptive dynamics; evolutionary singular strategy; stability analysis